2020
DOI: 10.1111/1759-7714.13451
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose escalation with modified fractionation schedules for locally advanced NSCLC: A systematic review

Abstract: Concomitant chemo-radiotherapy (cCRT) with 60 Gy in 30 fractions is the standard of care for stage 111 non-small cell lung cancer (NSCLC). With a median overall survival of 28.7 months at best and maximum locoregional control rates of 70% at two years, the prognosis for these patients is still dismal. This systematic review summarizes data on dose escalation by alternative fractionation, which has been explored as a primary strategy to improve both local control and overall survival over the past three decades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…101 Recent SRs and MAs of randomized trials assessing radiation doses have been reported and demonstrate that common doses delivered for locally advanced NSCLC include 64 Gy and 66 Gy in 2 Gy fractions, with 1.8 Gy daily fractions to total 64.8 Gy or 66.6 Gy also used. 23,24 Furthermore, the ongoing phase III NRG Oncology RTOG 1308 trial uses 70 Gy in 2 Gy daily fractions as its standard dose. 183 Comparisons of 60 Gy in 2 Gy fractions with doses above 60 Gy but , 74 Gy specifically delivered in once-daily radiotherapy using 1.8-2.0 Gy fractions are lacking to date.…”
Section: Literature Review and Clinical Interpretationmentioning
confidence: 99%
“…101 Recent SRs and MAs of randomized trials assessing radiation doses have been reported and demonstrate that common doses delivered for locally advanced NSCLC include 64 Gy and 66 Gy in 2 Gy fractions, with 1.8 Gy daily fractions to total 64.8 Gy or 66.6 Gy also used. 23,24 Furthermore, the ongoing phase III NRG Oncology RTOG 1308 trial uses 70 Gy in 2 Gy daily fractions as its standard dose. 183 Comparisons of 60 Gy in 2 Gy fractions with doses above 60 Gy but , 74 Gy specifically delivered in once-daily radiotherapy using 1.8-2.0 Gy fractions are lacking to date.…”
Section: Literature Review and Clinical Interpretationmentioning
confidence: 99%
“…Second, when confirmed, most patients were in the late lung cancer stage. According to statistical data, a 5 year survival rate of patients with lung cancer is only close to 15.9%. Based on this, it is both urgent and challenging for researchers to seek potential molecular diagnostic biomarkers that are reliable and valuable.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that improving outcomes in stage III NSCLC may involve some form of hypofractionation in the context of systemic concurrent therapy. Studies of radiation dose escalation with modified fractionation schedules in this setting for locally advanced NSCLC were recently analyzed by Zehentmayr et al [18]. In this analysis, dose escalation above the conventional 60 Gy using modified radiation fractionation schedules and shortened overall treatment time yielded similar OS and local regional control regardless of treatment sequence.…”
Section: Discussionmentioning
confidence: 99%